The Relation Between Consumption Patterns Snacks, Sugary Drinks and Physical Activity With Body Mass Index - Sarita, Rahma; Maigoda, Tonny C; Okfrianti, Yenni; Wahyudi, Anang; Yulianti, Risda (Poltekkes Kemenkes Riau, 2024)
Nutritional status reflects condition body resulting from consumption of food and nutrients that function as a source of energy, growth, development, tissue repair, and regulators of the body's metabolism. Nutritional status influenced various factors as daily diet, intake and lifestyle, types of drinks consumed, and physical activity. Purpose study determine relationship between consumption patterns snacks, sweet drinks and physical activity with body mass index D3 students majoring in nutrition at Poltekkes kemenkes bengkulu in 2024. Study used analytical descriptive design crossectional design. Sample of 46 people was selected random sampling technique. Data were analyzed univariately and bivariately using Chi-Square a significance level α=0.05. Consumption pattern of snacks, sugary drinks and physical activity with body mass index was significant. Relationship between consumption snacks with BMI p-value 0.001, consumption sugary drinks with BMI p-value 0.004, physical activity and BMI p-value 0.002.